The school libraries of the Augustinian sisters of the Philippines in Luzon a survey with implications for library service development - Cadelina, Rosario T.
Suggestions and recommendations are offered to help upgrade the school libraries through the combined effort and assistance of the school administrators, librarians and the congregation as well.